2010
DOI: 10.3171/2010.5.peds1010
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical treatment of progressive posthemorrhagic ventricular dilation in preterm infants: a 10-year single-institution study

Abstract: Object Intraventricular hemorrhage (IVH) and progressive posthemorrhagic ventricular dilation (PPHVD) may result in significant neurological morbidity in preterm infants. At present, there is no consensus regarding the optimal timing or type of neurosurgical procedure to best treat PPHVD. Conflicting data exist regarding the relative risks and benefits of two commonly used temporizing neurosurgical procedures (TNPs), ventricular access devices ([VADs] or ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 18 publications
4
95
2
1
Order By: Relevance
“…Previous studies have not found an association between the type of device used and infection rates; however, these reports combine positive CSF cultures and positive device cultures in one outcome measure and do not separately examine incidences of positive CSF cultures and overt device infection requiring removal. 12,13,31 Despite trends in CSF culture positivity, there were no differences in the rates of device removal between the reservoir and VSGS patients. Consequently, there were reservoir patients with positive CSF cultures who were treated without readily removing the device compared with VSGS patients, which may have reflected different practice patterns between the 2 time periods.…”
Section: Infection Risksmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have not found an association between the type of device used and infection rates; however, these reports combine positive CSF cultures and positive device cultures in one outcome measure and do not separately examine incidences of positive CSF cultures and overt device infection requiring removal. 12,13,31 Despite trends in CSF culture positivity, there were no differences in the rates of device removal between the reservoir and VSGS patients. Consequently, there were reservoir patients with positive CSF cultures who were treated without readily removing the device compared with VSGS patients, which may have reflected different practice patterns between the 2 time periods.…”
Section: Infection Risksmentioning
confidence: 94%
“…Two other reports have also demonstrated a higher, but not statistically significant, rate of permanent shunting in VSGS patients. Limbrick et al 13 noted shunt rates of 75.4% in reservoir patients and 66.7% in VSGS patients. Lam and Heilman 12 found that 93.75% of their reservoir patients had VP shunts placed, compared with 71.4% of VSGS patients.…”
Section: Vp Shunting Ratesmentioning
confidence: 97%
“…16 In a 10-year single-institution study, 29% of infants with severe IVH (Grades III and IV) developed symptomatic hydrocephalus requiring surgical intervention; 21% required permanent shunt insertion. 15 Ventriculoperitoneal (VP) shunt placement is the standard treatment for symptomatic PHHP after temporizing measures have enabled the patient to reach sufficient weight for definitive CSF diversion. Many studies have shown that the complication rate of ventriculoperitoneal shunts in the PHHP population is higher than that in patients with hydrocephalus from other etiologies.…”
mentioning
confidence: 99%
“…Rather, a variety of approaches, ranging from serial lumbar punctures (LP), transcutaneous transfontanellar puncture, external ventricular drainage, and ventriculosubgaleal shunt (with or without subcutaneous reservoir) to the endoscopic third ventriculostomy are used 4,6,7,8,9,10,11,12,13 . Ventriculoperitoneal (VP) shunts are contraindicated as a first option in low birth-weight (< 1.500g) premature neonates due to the higher risk of complications associated with the implanted prosthesis and are reserved for selected cases 4,9,11,13 . The scope of this study was describing a case series of premature neonates with PHH and assessing the outcomes of different approaches used for CSF diversion.…”
Section: Introductionmentioning
confidence: 99%